2016
DOI: 10.1186/s40411-016-0027-4
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing extended finite state machine configurations using predicate abstraction

Abstract: Background: Extended Finite State Machines (EFSMs) provide a powerful model for the derivation of functional tests for software systems and protocols. Many EFSM based testing problems, such as mutation testing, fault diagnosis, and test derivation involve the derivation of input sequences that distinguish configurations of a given EFSM specification. Method and Results: In this paper, a method is proposed for the derivation of a distinguishing sequence for two explicitly given or symbolically represented, poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
6

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
0
8
0
6
Order By: Relevance
“…Недетерминированные автоматы появляются и при рассмотрении предикатных абстракций расширенных автома-тов [16]; при построении различающих последовательностей такие абстракции ока-зываются наиболее эффективными при отсутствии входных параметров.…”
Section: построение различающих последовательностей для расширенных аunclassified
See 2 more Smart Citations
“…Недетерминированные автоматы появляются и при рассмотрении предикатных абстракций расширенных автома-тов [16]; при построении различающих последовательностей такие абстракции ока-зываются наиболее эффективными при отсутствии входных параметров.…”
Section: построение различающих последовательностей для расширенных аunclassified
“…Упрощая утверждение из работы [16] для случая различимости начальных конфигураций двух расширенных автоматов, получаем, что два расширенных автомата различимы (адаптивной) входной последовательностью α, если начальные состояния соответ-ствующих предикатных абстракций разделимы последовательностью α (адаптивно различимы), т.е. множества выходных реакций на α в этих состояниях не пересека-ются (существует адаптивный различающий тестовый пример [15]).…”
Section: построение различающих последовательностей для расширенных аunclassified
See 1 more Smart Citation
“…As shown in [19], in this case, a distinguishing sequence will be constructed for two nondeterministic FSMs. It is also the case when predicate abstractions are considered when deriving a distinguishing sequence [20]. One of simple ways is to use l-equivalents of an EFSM which describe the EFSM behavior under critical (parameterized) input sequences of length up to l. In the paper [10], it is experimentally shown that when two EFSMs differ in a small number of transitions (the specification EFSM and a mutant EFSM with one or two mutation transitions) usually it is enough to consider l = 2, 3 when deriving a distinguishing sequence.…”
Section: Preliminariesmentioning
confidence: 99%
“…In the automotive applications, the behaviors of some controllers [18] depend on the truth values of predicates defined over input variables with infinite domains. Extensions of FSMs with symbolic inputs and arithmetic operations on variables have been proposed [3,21,14] to relax limitations of the classical FSM and used in developing testing methods [9,21,14]. Following the same trend, our test generation method by constraint solving from FSM in [19,20] could be enhanced to extended FSM.…”
Section: Introductionmentioning
confidence: 99%